The effect of hydrogen enrichment on explosive limits in liquefied petroleum gas - Noor Shahirah, Shamsul (2010)
The use of hydrogenated fuels shows considerable promise for applications in gas turbines and internal combustion engines. The aims of this study are to determine the explosive limits of liquefied petroleum gas/air mixture and to investigate the effect on explosive limits liquefied petroleum gas/air mixture enriched up to 8 vol % hydrogen by total volume at atmospheric pressure and ambient temperature. The experiments were performed in 20 Liter closed explosion vessel. The mixtures were ignited by using spark permanent wire that placed at the centre of the vessel. The pressure-time variations during explosion of liquefied petroleum gas/air mixture in explosion vessel were recorded. The explosion pressure data is used to determine the explosive limits which flame propagation is considered to occur if explosion pressure greater than 0.1 bar. In this study the result shows the explosive limits is from 2 to 8 vol % of liquefied petroleum gas/air mixture and have revealed that the addition of hydrogen in liquefied petroleum gas/air mixture decreases the lower explosive limits from 2 to 1 vol % and for the upper explosive limits, the limits is also decrease from 8 to 7 vol %.